The impact of social support on the risk of eating disorders in women exposed to intimate partner violence - Schirk DK; Lehman EB; Perry AN; Ornstein RM; McCall-Hosenfeld JS (Dove Medical Press, 2015)
Dana K Schirk,1 Erik B Lehman,2 Amanda N Perry,3 Rollyn M Ornstein,4 Jennifer S McCall-Hosenfeld2,5 1The Pennsylvania State University College of Medicine, 2Department of Public Health Sciences, The Pennsylvania State University College of Medicine, Hershey, 3Department of Agricultural Economics, Sociology, and Education, Division of Rural Sociology, College of Agriculture, Pennsylvania State University, University Park, 4Department of Pediatrics, 5Department of Medicine, The Pennsylvania State University College of Medicine, Hershey, PA, USA Background: Eating disorders (EDs) are often found among women exposed to intimate partner violence (IPV). The role of social support (SS) as a protective factor against ED among IPV-exposed women is not firmly established.Objective: The objective of this study is to determine the distribution of risk of EDs among women exposed to IPV and to examine the impact of SS on risk of ED among IPV-exposed women.Methods: Women (aged 18–64 years) exposed to IPV during their lifetimes (defined by the Humiliation–Afraid–Rape–Kick instrument) were recruited from primary care and domestic violence service agencies and surveyed on demographics, mood/anxiety disorders, psychosocial/community factors, and strategies used in response to IPV. The Eating Disorder Screen for Primary Care assessed the risk of ED. A modified Medical Outcomes Study Social Support Survey assessed overall functional support (scale range: 0–32; categorized into quartiles). Ordinal logistic regression examined the risk of ED based on SS, controlling for prespecified demographics (age, race/ethnicity, marital status, near-poverty level), and health-related factors significant in bivariate analyses (risky alcohol use).Results: Among 302 women with lifetime IPV, 41 (14%) were at high risk, 127 (42%) were at moderate risk, and 134 (44%) were at low risk of an ED. In bivariate analyses, high risk of an ED was significantly more frequent among women with a low SS score (<19, 24%) versus a high SS score (≥30, 12%) (P=0.03). High risk of an ED was significantly associated with risky alcohol use (18%) versus non-risky alcohol use (13%; P=0.008). In multivariable analysis, a 5-unit increase in overall SS was significantly associated with decreased odds of ED risk (P=0.007).Conclusion: Among IPV-exposed women, low SS is associated with an increased risk of ED. SS may protect against ED by reducing anxiety and promoting positive actions, but further study is needed to confirm this. Keywords: women, domestic violence, spouse abuse, social support, eating disorders